Dispersion of tongka langit banana in Buru and Seram, Maluku Province, Indonesia, based on topographic and climate factors - HALVINA GRASELA SAIYA; Adriana Hiariej; ANNEKE PESIK; ELIZABETH KAYA; MEITTY LOUISE HEHANUSSA; FERAD PUTURUHU (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Saiya HG, Hiariej A, Pesik A, Kaya E, Hehanussa ML, Puturuhu F. 2020. Dispersion of tongka langit banana in Buru and Seram, Maluku Province, Indonesia, based on topographic and climate factors. Biodiversitas 21: 2035-2046. The aim of this research is to understand the dispersion of tongka langit banana as one of the important endemic species in Maluku and also to know the topographic and climate factors hypothetically influencing the dispersion of tongka langit banana. The associated environmental factors are an initial approach that can be used to assess why the species only exists in certain locations. The data of coordinates were collected from survey activity; meanwhile, the slope and contour data were from the Shuttle Radar Topographic Mission (SRTM); and the climate data were from Meteorology, Climatology, and Geophysical Agency through statistic data publication. Then, all data were analyzed using Remote Sensing and GIS methods. The results showed that in Buru Island, tongka langit bananas were found in four locations, with climate condition was rather wet and found on slope grade of 0-8% and 8-15%. Whereas in Seram Island, tongka langit bananas were found in fifteen locations, with wet climate conditions, and on the same condition of slope as those found in Buru island.